MEMBANGUN KOMPETENSI ORGANISASI PENINGKATAN KINERJA PERGURUAN TINGGI SWASTA - Hidayat, Dwi Suryanto (PRESTASI, 2011)
AbstractThe objective is to test whether there are effects of organizational learning, external environment and reputation toward organization competency. Further, to see if there is effect of this competency towards the organizationâs performance.This research had theoretical and managerial implication. Theoretically, this study justified previous research findings that organizational learning, external environment and reputation contributed positively and significantly to organization competency. The managerial implication was for the leaders of higher education organizations to always support organizational learning, observe and adapt to external environment change, and create good reputation in order to excel in the competency. This would also create performance for sustainable competitive advantage.Keyword: Â Â Â Â Â Â Â  organizational learning, business environment, reputation, competency, performance, competitive advantage.